Bifurcation analysis of a product inhibition model of a continuous fermentation process - Yongwimon Lenbury (2018)
A product inhibition model of a continuous fermentation process is considered. If the yield term is a variable function of ethanol concentration, oscillation in the cell and ethanol concentrations is shown to be a Hopf bifurcation in the underlying system of nonlinear, ordinary differential equations which comprises the model. © 1987 Springer-Verlag.